Simulations of tidal turbine blade loading in flood and ebb tides - Vogel, CR; Tang, T; Dubon, SL; Steynor, J (International Marine Energy Journal, 2021)
Tidal turbines are deployed for extended periods in a harsh environment with significant levels of flowinduced unsteady loading. The contributions of these loads to fatigue damage of the turbine blades is not well understood, contributing to over-engineered structures with attendant cost penalties in order to avoid premature failure. In this paper, we investigate computationally the effect of the velocity shear profile during the flood and ebb tides on the unsteady loading of a tidal turbine. The flow profiles are based on data from the Fall of Warness, UK. Actuator line simulations of a fixed-speed turbine were performed to evaluate the spanwise blade loading distribution and blade root shear forces and bending moments. The magnitude of load fluctuations were observed to increase with flow speed due to the larger onset flow variation across the rotor plane. This effect was amplified during the flood tide due to the greater shear across the rotor plane, reaching almost 20% at a hub-height flow speed of 3.0 ms−1, whereas a surface stress during the ebb tide acted to suppress the variation in flow speed across the rotor plane. This was also reflected in the blade root shear force and bending moments, with greater azimuthal variation experienced during flood tides than in the ebb tide. The spanwise load distributions generated in this work are being used to define the loads that will be applied to a decommissioned tidal turbine blade in the accelerated cyclic blade testing facility FastBlade.